The Role of Personal Values in Forming Students’ Entrepreneurial Intentions in Developing Countries - Karimi, Saeid; Makreet, Ahmad Salman (Frontiers in Psychology, 2020)
The purpose of this study was to examine the mechanisms through which the personal values are associated with the entrepreneurial intention, by integrating the theory of the human values into the theory of the planned behavior. Data were collected using a questionnaire from a sample of 452 agricultural students who were selected from the two public universities in two Persian-speaking countries, namely, Iran and Afghanistan. The results of the structural equation modeling showed that the personal values of the openness to change and the self-enhancement are not directly related to the entrepreneurial intention. However, these personal values were indirectly related to the entrepreneurial intention through attitudes toward entrepreneurship and the controlled behavioral control. The results also showed that there was not a significant difference between the two countries according to the relationship between the personal values and the motivational variables of the theory of the planned behavior (i.e., the attitude toward the entrepreneurship, the subjective norms, the perceived behavioral control and the entrepreneurial intention) and the relationship between the motivational variables and the entrepreneurial intentions. Based on the results, it was suggested that the educators of the potential entrepreneurs should try more to stimulate the personal values which foster the entrepreneurial intention and its antecedents.